Activity Guided Isolation of Nematicidal Constituents from the Roots of Berberis brevissima Jafri and Berberis parkeriana Schneid - İshrat Naz; Muhammad Alamzeb; Mamoon Urrashid; Saqib Ali (Journal of Agricultural Sciences)
Biological screening of different parts of the selected Berberis species (B. brevissima Jafri and B. parkeriana Schneid) showed that methanolic root extract possessed significant efficacy against Meloidogyne javanica (a root knot nematode). From root methanolic extracts of selected Berberis species four isoquinoline alkaloids; jatrorrhizine, dehydrocheilnthifoline, berberine and berberrubine were isolated. Structures of the isolated compounds were determined by using EIMS, 1H and 13C NMR, and other 2D spectroscopic techniques. Percentage juveniles mortality of M. javanica was determined at various concentrations (100, 200 and 300 µg mL-1) using carbofuran as control. Berberine possessed the highest nematicidal activity (71.33%) followed by jatrorrhizine (59.50%). The in vitro results suggested that these compounds from Berberis species could be potential novel nematicides against M. javanica.